THE USE OF REGIONAL ANESTHESIA IN ELECTIVE LAPAROSCOPIC SURGERY IN PATIENTS WITH ABDOMINAL PATHOLOGY - Ibragimov N. K.; Ramazanova Z. F.; Muralimova R.S.; Nishonov M. R. (Galaxy International Interdisciplinary Research Journal, 2023)
Laparoscopic surgical interventions are low-traumatic operations, but with a pronounced postoperative pain syndrome, often this pain on the first day exceeds the pain that occurs in the postoperative period in patients after traditional surgical intervention. The presence of a pronounced pain syndrome is an obstacle to early postoperative rehabilitation within the framework of fast-track surgery or ERAS (Enhanced Recovery After Surgery) programs . In this connection, it became necessary to use other methods of anesthetic management, which allows not only to quickly remove the patient from anesthesia without any side effects from narcotic drugs and opiates, but also to manage anesthesia both in the surgical period and in the perioperative one .